(untitled) - Barker, A.A.J. (Arthur Adrian Johnson)

Architectural authenticity in the Western Cape : a precognition of the Fifth Cape Vernacular (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2024.